Free Lunch Program For Students In Several Countries And Valuable Lessons For Indonesia Preparing The Golden Generation Of 2045 - Hilery, Putri Melina; Rumambi, Freddy Johanis; Hadiningrat, K.P. Suharyono S.; Pakpahan, Marisi (STABN RADEN WIJAYA WONOGIRI, 2024)
Improving the quality of human resources is Indonesia's main goal to achieve Golden Generation status by 2045. This research analyzes different lunch program models that have been successfully implemented in countries such as Finland, Japan, Brazil, and India. The analysis shows that the success of these programs does not only depend on nutritional aspects; integrated nutrition education, parental participation, and support from the government and community are also important. In schools, nutritious food is very important for the health and cognitive development of students as well as for improving their academic performance. This research found challenges and opportunities for Indonesia in implementing similar programs. This research uses a qualitative approach. The recommendations made include enhancing educator training, implementing policies that support the provision of healthy food in schools, and raising public awareness about the importance of good nutrition for children. By taking valuable lessons from other countries, it is hoped that Indonesia can develop an efficient and sustainable lunch program. This will improve students' health and help build a competitive generation to achieve the Golden Generation 2045.